Phosphoric Acid Invasion in High Temperature PEM Fuel Cell Gas Diffusion Layers. (10th December 2017) - Bevilacqua, N.; George, M.G.; Galbiati, S.; Bazylak, A.; Zeis, R.
Graphical abstract: Abstract: In this work, liquid phosphoric acid was injected into polymer electrolyte membrane fuel cell (PEMFC) gas diffusion layers (GDLs) to visualize the invasion patterns developed at breakthrough. Three-dimensional (3D) images of the GDLs were obtained through X-ray computed tomography, and equivalent pore networks were generated as the basis for pore network simulations using OpenPNM. Strong qualitative agreement was obtained between the simulated and experimentally observed liquid phosphoric acid invasion patterns, which provided validation for the numerical modeling. Different GDL materials were evaluated by examining the effects of a micro porous layer (MPL) and pore size distribution on the saturation and distribution of phosphoric acid. The MPL was shown to restrict liquid phosphoric acid from entering the carbon fiber substrate. The overall phosphoric acid saturation at breakthrough was found to decrease significantly for samples containing an MPL due to the smaller pore sizes. Further, the influence of cracks in an MPL on overall saturation at breakthrough was investigated. It was observed that a crack-free MPL provided a more effective physical barrier to restrict the undesired leaching of liquid phosphoric acid through the GDL.